The Road to Freedom: An Exploration of Alternative Healing and Spirituality in the Context of the Post-Socialist Transition in the Czech Republic. - Hoskova, Barbora. (Tufts Archival Research Center, 2016)
This paper examines the alternative healing and spirituality community in the Czech Republic in light of the country’s post-socialist transition. It locates alternative healing and spirituality within a multi-layered system of care through an analysis of people’s pathways to these alternatives, which positions these practices and beliefs as complementary to conventional systems of care and belief. A subsequent exploration of alternative healing and spirituality as an integral part of people’s lives reveals freedom as a central aspect of these practices and beliefs. Thus this paper also argues that alternative healing and spirituality exist in dialogue with the post-socialist political discourse of freedom, not only functioning as complements for the conventional systems of care and belief, but also providing alternative conceptualizations and narratives of freedom. As explored within the paper, these narratives illustrate and engage with the lived realities in the Czech Republic that are overlooked or unaccounted for by the political discourse. This paper therefore illustrates not only the role that alternative healing and spirituality play within the Czech systems of care and belief, but also the ways in which people within the alternative healing and spirituality community in the Czech Republic reimagine freedom and their roles as citizens and members of society.